Evaluasi Kenyamanan Termal pada Lanskap Jalan Prof. Dr. Ida Bagus Mantra, Bali - Setiawan, Made Ary Suta; Asmiwyati, I Gusti Agung Ayu Rai; Krisnandika, Anak Agung Keswari (Jurnal Arsitektur Lansekap; Vol.9, No.2, Oktober 2023, 2023)
Evaluation of Thermal Comfort in Prof. Dr. Ida Bagus Mantra Streetscape, Bali. Vegetation hold an important role in a streetscape, one of which is the amelioration of the microclimate which afffect the user comfort, especially human thermal comfort on the streetscape. Prof. Dr. Ida Bagus Mantra street has several different parts when viewed from the variation of the shade trees used. This study sought to determine the best fit composition of the shade trees to increase human thermal comfort in Prof. Dr. Ida Bagus Mantra street. Six sample of streetscape will be studied in three different composition of shade trees type. On these street, air temperature and humidity will be measured to calculate the level of human thermal comfort using Thermal Humidity Index (THI). The results showed that streetscapes with three rows of shade trees had a lower THI value compared to streetscapes with only one row of shade trees, and the streetscapes planted with spreading crowns shade trees had lower THI values than streetscapes planted with rounded crowns trees. Based on this, it is recommended to plant shade trees on the median and both sides of the road with trees that have dense leaf mass and can give a unique impression if planted in mass.